The Relationship between Malaysian Counselors’ Multicultural Counseling Competence and Client Satisfaction - Voon, Siok Ping; Rafidah Aga, Mohd Jaladin (University of Malaya, 2013)
The study investigated Malaysian counselors’ self-perceived Multicultural Counseling Competence (MCC) and its relationship with clients’ satisfaction. A total of 104 participants (52 counselor-client dyads) completed the survey. Of the 52 dyads, 26 were registered and licensed counselors in Malaysia (professional counselors) and another 26 were internship students (paraprofessional counselors). The Multicultural Awareness-KnowledgeSkills-Survey-Counselor Edition-Revised (MAKSS-CE-R) and Client Satisfaction Questionnaire-8 (CSQ-8) were the primary measures utilized. Main findings revealed that there was a significant positive relationship between counselors’ MCC and client satisfaction, r = .418, p = .002 and there was no significant difference between professional and paraprofessional counselors on MCC and client satisfaction. Future directions in research based on the limitations of current study and implications for counseling were discussed